RhoGDI1 regulates cell-cell junctions in polarized epithelial cells - Wibbe, Nicolina; Steinbacher, Tim; Tellkamp, Frederik; Beckmann, Niklas; Brinkmann, Frauke; Stecher, Manuel; Gerke, Volker; Niessen, Carien M.; Ebnet, Klaus (Frontiers in Cell and Developmental Biology, 2024)
Cell-cell contact formation of polarized epithelial cells is a multi-step process that involves the co-ordinated activities of Rho family small GTPases. Consistent with the central role of Rho GTPases, a number of Rho guanine nucleotide exchange factors (GEFs) and Rho GTPaseactivating proteins (GAPs) have been identified at cell-cell junctions at various stages of junction maturation. As opposed to RhoGEFs and RhoGAPs, the role of Rho GDP dissociation inhibitors (GDIs) during cell-cell contact formation is poorly understood. Here, we have analyzed the role of RhoGDI1/ARHGDIA, a member of the RhoGDI family, during cell-cell contact formation of polarized epithelial cells. Depletion of RhoGDI1 delays the development of linear cell-cell junctions and the formation of barrier-forming tight junctions. In addition, RhoGDI1 depletion impairs the ability of cells to stop migration in response to cell collision and increases the migration velocity of collectively migrating cells. We also find that the cell adhesion receptor JAM-A promotes the recruitment of RhoGDI1 to cell-cell contacts. Our findings implicate RhoGDI1 in various processes involving the dynamic reorganization of cellcell junctions.